Philippines Urbanization Review : Fostering Competitive, Sustainable and Inclusive Cities - World Bank (World Bank, Washington, DC, 2017)
Urbanization is a driving force for growth and poverty reduction. Globally, over 80 percent of economic activity is concentrated in cities, and cities are essential for lifting millions of people out of poverty through the opportunities that density and agglomeration can bring with jobs, services, and innovation. However, if not carefully managed and planned for, the benefits of urbanization are not realized and can result in congestion, slums, pollution, inequality and crime. City competitiveness is an important part of successful urbanization. A competitive city facilitates its firms and industries to create jobs, raise productivity, and increase the incomes of citizens over time. At the same time, it is not possible to achieve these objectives without strong institutions, social inclusion, resilience, and environmental sustainability. All of these elements are important to harnessing the benefits of urbanization and must be enabled by both national and local governments. Chapter one of the report provides an introduction to urbanization in the Philippines. Chapter two covers analysis of urbanization and growth in the Philippines, Chapter three focuses on city competitiveness for economic development and job creation, chapter four provides an analysis of urban poverty with a particularly focus on informal settler families (ISFs) in Metro Manila, chapter five outlines the key binding constraints related to institutions for urban development and metropolitan governance; and chapter six covers constraints related to land administration and management in urban areas. Each chapter includes a framework for analysis, identification and assessment of key issues, and provides recommendations for the Government of the Philippines to consider. Important topics related to environmental sustainability and resilience are included as a cross cutting issue as they relate to urban planning and land management, but not covered in depth as they have been addressed in other World Bank reports. The full study is summarized below. Background technical papers for each section have also been prepared and cover much more analysis and detail. These are available as a companion to this policy report.